Glimpses of Indian agriculture : macro and micro aspects - Jharwal,S.M.(Editor) Deshpande,R.S.(Editor) Malik,R.P.S.(Editor) Jha,Brajesh.(Editor) Sharma,Vijay Paul.(Editor) (Academic Foundation in association with Directorate of Economics and Statistics, Dept. of Agriculture and Cooperation, Ministry of Agriculture, Govt. of India and Agricultural Development and Rural Transformation Centre, Institute of Social and Economic Change, 2008)
Contributed articles.